PENGARUH INFORMATION RISK TERHADAP COST OF CAPITALBADAN USAHA NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Shirlen Nathania Fuandy; Werner Ria Murhadi; Liliana Inggrit Wijaya (CALYPTRA, 2018)
Abstract- The purpose of this research was to know the influence of information risk (accrual quality, beta, leverage, size, growth, ROA, interest coverage, and NIBE) as an independent variable to cost of debt and cost of equity as a dependent variable to company listed in Bursa Efek Indonesia period 2012-2014. There were total 249 observations in this research that consist of 83 companies, which were listed in Bursa Efek Indonesia period 2012-2014. The result of this research showed that accrual quality and leverage had a positive influence towards cost of equity, beta and size were negative towards cost of equity, while growth was not significant towards cost of equity. More results showed that accrual quality and size were positive towards cost of debt, while interest coverage and NIBE were negative; leverage and ROA were not affected by cost of debt of a company.